2020
DOI: 10.1111/anec.12806
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiogram analysis of patients with different types of COVID‐19

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 12 publications
4
75
0
3
Order By: Relevance
“…After sinus tachycardia, atrial fibrillation ( Fig. 1 ) is the next most commonly seen SVT [ [40] , [41] , [42] ]; atrial fibrillation can present in a number of different fashions, including new-onset, recurrence of a pre-existing dysrhythmia, and persistence of permanent atrial fibrillation with new rapid ventricular response. In the majority of patients with significant COVID-19 infection and atrial fibrillation, the rate will be quite rapid, thus the ECG will demonstrate atrial fibrillation with rapid ventricular response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After sinus tachycardia, atrial fibrillation ( Fig. 1 ) is the next most commonly seen SVT [ [40] , [41] , [42] ]; atrial fibrillation can present in a number of different fashions, including new-onset, recurrence of a pre-existing dysrhythmia, and persistence of permanent atrial fibrillation with new rapid ventricular response. In the majority of patients with significant COVID-19 infection and atrial fibrillation, the rate will be quite rapid, thus the ECG will demonstrate atrial fibrillation with rapid ventricular response.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of patients with significant COVID-19 infection and atrial fibrillation, the rate will be quite rapid, thus the ECG will demonstrate atrial fibrillation with rapid ventricular response. Both sinus tachycardia and atrial fibrillation are independent predictors of illness severity, myocardial injury, and poor outcomes in COVID-19 [ 40 ]. One study conducted in New York hospitals found atrial fibrillation/flutter was present in 14.3% of patients at admission and occurred in 10.1% of patients during hospitalization [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the incidence of new-onset or paroxysmal AF in COVID-19 is not well known yet. While the rate of new-onset AF/AFL in all AF/AFL cases was above 40% in some studies [ 19 , 20 ], new-onset AF/AFL was not reported among all AF/AFL cases in some other studies [ 11 , 22 ]. New-onset AF was not observed in our cohort during in-hospital follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the our findings, this study found an independent association between AF or AFL and all-cause mortality [ 20 ]. In addition, another cohort study conclude that AF was the independent risk factor of in-hospital death and ventilator use in patients with COVID-19 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%